Fully localised edge states in boundary layers - Khapko, Taras; Kreilos, Tobias; Schlatter, Philipp; Duguet, Yohann; Eckhardt, Bruno; Henningson, Dan S. (Proceedings - 15th European Turbulence Conference, ETC 2015, 2015)
Investigation of the laminar–turbulent boundary is performed in a boundary-layer flow. Constant homogeneous suction is applied at the wall in order to prevent the spatial growth of the layer, leading to the parallel Asymptotic Suction Boundary Layer (ASBL). Edge tracking is performed in a large computational domain allowing for full spatial localisation of the structures on the laminar–turbulent separatrix. The obtained dynamics of the state goes through calm and bursting phases. During the latter the structure grows in size, shedding vortices downstream of its core which viscously decay during the calm phases. Comparison with the computation in spatially growing boundary layer is made. The influence of the Reynolds number and the path leading from the edge state to turbulent flow are considered.
CRIS-Team Scopus Importer:2023-03-21